TUMBUHAN BERKHASIAT OBAT MASYARAKAT DAYAK MERATUS BALAI ADAT CABAI DESA PATIKALAIN KECAMATAN HANTAKAN KABUPATEN HULU SUNGAI TENGAH - Abdullah Abdullah; Kissinger Kissinger; Abdi Fithria (Lambung Mangkurat University-Indonesia, 2020)
Meratus Mountain,which lies across some regencies of South Borneo, is a forest area considered as main source of society who resides in the area. Dayak Meratus Ethnic Balai Adat Cabai of Patikalain Hantakan, Hulu Sungai Tengah, South Borneo is one of the communities whose life depends on the forest of Meratus Mountain. The utilization of plants as medicine by society is conducted by selecting and designating the plant variety to heal certain disease, the taking method, the process, and the usage. Each of them would be varied in every ethnic. This study aimed at analyzing the medicinal plants utilization of Dayak Meratus Society Balai Adat Cabai of Patikalain, Hantakan, Hulu Sungai Tengah, South Borneo. The result of this study found that 32 varieties of plants were utilized as medicine of 24 different families